Zuo-Gui-Wan Aqueous Extract Ameliorates Glucocorticoid-Induced Spinal Osteoporosis of Rats by Regulating let-7f and Autophagy - Shen, Gengyang; Shang, Qi; Zhang, Zhida; Zhao, Wenhua; Chen, Honglin; Mijiti, Ibrayinjan; Chen, Guifeng; Yu, Xiang; Yu, Fuyong; Zhang, Peng; He, Jiahui; Zhang, Xuelai; et al. (Frontiers in Endocrinology, 2022)
Objective This study proposes to explore the protective effect of Zuo-Gui-Wan (ZGW) aqueous extract on spinal glucocorticoid-induced osteoporosis (GIOP) in vivo and in vitro, and the underlying mechanisms of ZGW in GIOP and osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) were conducted. Methods In vivo, SD rats were randomly divided into three groups: control group (CON), dexamethasone (DEXM) group, and ZGW group, which were given vehicle, DEXM injection, and ZGW intragastric administration at the same time. Vertebral bone microarchitecture, biomechanics, histomorphology, serum AKP activity, and the autophagosome of osteoblasts were examined. The mRNA expressions of let-7f, autophagy-associated genes (mTORC1, Beclin-1, ATG12, ATG5, and LC3), Runx2, and CTSK were examined. In vitro, the let-7f overexpression/silencing vector was constructed and transfected to evaluate the osteogenic differentiation of BMSCs. Western blot was employed to detect the expression of autophagy-associated proteins (ULK2, ATG5, ATG12, Beclin-1, LC3). Results In vivo, ZGW promoted the bone quantity, quality, and strength; alleviated histological damage; increased the serum AKP activity; and reduced the autophagosome number in osteoblasts. Moreover, ZGW increased the let-7f, mTORC1, and Runx2 mRNA expressions and reduced the Beclin-1, ATG12, ATG5, LC3, and CTSK mRNA expressions. In vitro, bioinformatics prediction and dual luciferase reporter gene assay verified that let-7f targeted the binding to ULK2 and negatively regulated the ULK2 expression. Furthermore, by let-7f overexpression/silencing, ZGW may promote osteoblast differentiation of BMSCs by regulating let-7f and autophagy as evidenced by Western blot (ULK2, ATG5, ATG12, Beclin-1, LC3). Conclusions ZGW may ameliorate GC-induced spinal osteoporosis by promoting osteoblast differentiation of BMSCs by activation of let-7f and suppression of autophagy.